1992
DOI: 10.1039/dt9920003223
|View full text |Cite
|
Sign up to set email alerts
|

Structural considerations of terdentate ligands: crystal structures of 2,2′ : 6′,2″-terpyridine and 2,6-bis(pyrazol-1-yl)pyridine

Abstract: The crystal structures of the terdentate ligands 2,2' : 6',2"-terpyridine (terpy) and 2,6-bis(pyrazol-l -yl)pyridine (bppy) were determined by single-crystal diffraction studies. The compound terpy crystallizes in the non-centrosymmetric orthorhombic space group P2,2,2, with a = 3.947(1), b = 16.577(7) and c = 17.840(6) A; the structure was refined to R = 0.0745 for all 1087 independent data and R = 0.0470 for those 609 data with F > 60-(F). The compound bppy crystallizes in the centrosymmetric orthorhombic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 23 publications
7
96
0
Order By: Relevance
“…The cis N l mPt--N2 and N2--Pt--N3 angles are less than 90 ° [80.5 (3) and 81.3 (3) °, respectively], as is commonly observed in terpyridine complexes (e.g. Bailey, Catalano & Gray, 1993;Yip, Cheng, Cheung & Che, 1993;Jennette, Gill, Sadownick & Lippard, 1976;Aldridge, Stacy & McMillin, 1994 (Bessel et al, 1992). The Pt--N4 distance, 2.021 (6)A, is in good agreement with the expected value of 2.017/~,, which is the average Pt--N(imidazole) distance for 20 cases of Nalkylimidazole-platinum(II) tetracoordinated compounds [sample standard deviation 0.014A (Orpen et al, 1992)].…”
mentioning
confidence: 99%
“…The cis N l mPt--N2 and N2--Pt--N3 angles are less than 90 ° [80.5 (3) and 81.3 (3) °, respectively], as is commonly observed in terpyridine complexes (e.g. Bailey, Catalano & Gray, 1993;Yip, Cheng, Cheung & Che, 1993;Jennette, Gill, Sadownick & Lippard, 1976;Aldridge, Stacy & McMillin, 1994 (Bessel et al, 1992). The Pt--N4 distance, 2.021 (6)A, is in good agreement with the expected value of 2.017/~,, which is the average Pt--N(imidazole) distance for 20 cases of Nalkylimidazole-platinum(II) tetracoordinated compounds [sample standard deviation 0.014A (Orpen et al, 1992)].…”
mentioning
confidence: 99%
“…Resulting crystals were picked up and were washed several times. Structures of the crystals were confirmed as orthorhombic form by comparing the measured powder XRD pattern with a theoretical XRD pattern calculated using a crystal structure data [2] [3]. Melting point of the orthorhombic crystals was reported as 359 -361 K [1].…”
Section: Preparation Of Two Polymorphism Of Terpymentioning
confidence: 99%
“…Mutai et al, reported two crystal structures of 2,2':6',2"-terpyridine (Figure 1, expressed as terpy hereafter) [1]. In Figure 2, two crystal structures of terpy are shown using reported crystallographic data [2] [3]. A remarkable difference between the two crystal structures is their molecular packing motif.…”
Section: Introductionmentioning
confidence: 99%
“…The first reported 2,2 0 ;6 0 ,2 00 -terpyridine crystal structure was the unsubstituted compound (Bessel et al, 1992). Recently, the structure of the 4 0 -chloro-2,2 0 ;6 0 ,2 00 -terpyridine precursor (1) that was used to synthesize the title compound (3) was reported (Beves et al, 2006).…”
Section: Commentmentioning
confidence: 99%